NOTIFICATION!!! - Retrieved, Papers (European Scientific Journal, ESJ, 2017)
The full content of this special edition is retrieved from the conference proceedings published by the European Scientific Institute, ESI. http://eujournal.org/index.php/esj/pages/view/books The European Scientific Journal, ESJ, after approval from the publisher re publishes the papers in a Special edition.